Human disease caused by loss of fast IIa myosin heavy chain due to recessive MYH2 mutations. - Tajsharghi, H; Hilton-Jones, D; Raheem, O; Saukkonen, A; Oldfors, A; Udd, B (2010)
Striated muscle myosin heavy chain is a molecular motor protein that converts chemical energy into mechanical force. It is a major determinant of the physiological properties of each of the three muscle fibre types that make up the skeletal muscles. Heterozygous dominant missense mutations in myosin heavy chain genes cause various types of cardiomyopathy and skeletal myopathy, but the effects of myosin heavy chain null mutations in humans have not previously been reported. We have identified the first patients lacking fast type 2A muscle fibres, caused by total absence of fast myosin heavy chain IIa protein due to truncating mutations of the corresponding gene MYH2. Five adult patients, two males and three females, from three unrelated families in UK and Finland were clinically assessed and muscle biopsy was performed in one patient from each family. MYH2 was sequenced and the expression of the corresponding transcripts and protein was analysed in muscle tissue. The patients had early-onset symptoms characterized by mild generalized muscle weakness, extraocular muscle involvement and relatively favourable prognosis. Muscle biopsy revealed myopathic changes including variability of fibre size, internalized nuclei, and increased interstitial connective and adipose tissue. No muscle fibres expressing type IIa myosin heavy chain were identified and the MYH2 transcripts were markedly reduced. All patients were compound heterozygous for truncating mutations in MYH2. The parents were unaffected, consistent with recessive mutations. Our findings show that null mutations in the fast myosin heavy chain IIa gene cause early onset myopathy and demonstrate that this isoform is necessary for normal muscle development and function. The relatively mild phenotype is interesting in relation to the more severe phenotypes generally seen in relation to recessive null mutations in sarcomeric proteins.